The dual role of the contact system in bacterial infectious disease - Frick, Inga-Maria; Björck, Lars; Herwald, Heiko (Thrombosis and Haemostasis, 2007)
Hemostasis is a sensitive and tightly regulated process, involving the vascular endothelium and blood cells as well as factors of the coagulation and fibrinolytic cascades. Over the last four decades evidence has accumulated that during infection, inflammatory mediators from the microbe and/or host are capable to modulate the equilibrium between the procoagulant and anticoagulant status of the host. Dependent on the mode of activation, these changes can cause either local or systemic inflammatory reactions that may be beneficial or deleterious to the human host. The present review aims to present the state of the art with respect to the role of the contact system (also known as the intrinsic pathway of coagulation or the kallikrein/kinin system) in innate immunity and systemic inflammatory reactions.
Keywords: Coagulation; contact system; inflammation; infectious diseases; innate immunity